Effect of acidulated phosphate fluoride application on microhardness of glass ionomer cement - Izzudin, Mohammad Azrul; Karlina, Elin; Indriyanti, Ratna (Universitas Padjadjaran, 2015)
Introduction: Acidulated phosphate fluoride (APF) gels are commonly used as preventive caries materials in paediatric dentistry while glass ionomer cements (GICs) are widely used as a restorative material. The purpose of this study was to determine the effect of acidulated phosphate fluoride application towards the microhardness of GIC. Methods: This study was an experimental laboratory study where ten specimens were prepared from high viscosity GIC, which was Fuji IX. Specimens were stored in 50 ml distilled water at first 24 hours at 37°C, and then specimens were divided into fluoride group which was immersed in 25 ml of 1.23 % APF gel and control group which was stored 25 ml distilled water for 24 hours at 37°C. The Micromet II Microhardness Tester, Buehler, IL, USA that was standardised for Vickers hardness test was used to test the specimens at 100-gram load. Data were analysed using the t-test comparison test. Results: The level of microhardness of the fluoride group (14.34) was much lower compared to the control group (43.21) with a highly significant difference (p<0.01). Conclusion: The application of 1.23% APF gel on high viscosity GIC reduces the microhardness level compared to the control group.